Permanência e êxito no ensino médio integrado: um estudo de caso no Instituto Federal de Alagoas - Costa, Ana Maria Leal (2021)
The permanency and success of young people in high school have been the source of studies by several authors. In the same sense, public policies are adopted in an attempt to reduce dropout and abandonment, which are common in the academic path. The present work aims to know and relate the relevant factors regarding the permanence and success of students in integrated high school courses at the Instituto Federal de Alagoas (IFAL), Maceió Campus, through the sociological characterization of their social and educational pathways. Following the qualitative methodology and analytical method of case study, we seek to investigate which factors provide the permanence and school success and what is in common among the students of the last years that supports achieving academic success. To investigate which relationships exist between the investigated factors and success in studies, as well as to know what leads students with a low socioeconomic level to be resilient when faced with adversities in the student environment were the strands of this research. It is worth mentioning that the pandemic caused by the covid-19 resulted in limitations in the course of the research application, being necessary to make some adjustments due to the sanitary conditions implemented worldwide. In order to understand the studied phenomenon, lives were performed, people's speeches were recorded, data to support the study were researched in documents generated by the institution, preliminary conversations with the pedagogical team were held, and online meetings were held. The results reveal evidence in the relationship between the cultural capital of families and academic performance, and point to signs of the influence of school interaction in the permanence of students in IFAL. However, the product of this research also reveals the need to modify strategies and methodologies regarding the teaching and structuring of courses, leading to the suggestion to direct educational policies that favor increasing the income of students' families, such as expanding the granting of scholarships. Such actions may increase the possibility of a larger number of students with a successful experience in the institution